Supplemental Figure 1 from Multicenter Phase I Trial of Ivosidenib as Maintenance Treatment Following Allogeneic Hematopoietic Cell Transplantation for IDH1-Mutated Acute Myeloid Leukemia - Amir T. Fathi (15313195) (2025)
Supplemental Figure 1: Overall and progression-free survival for patients, according to whether the transplant followed first line or second line treatment.